Television viewing in Thai infants and toddlers: impacts to language development and parental perceptions - Kriweradechachai Suntree; Mo-suwan Ladda; Chuthapisith Jariya; Ruangdaraganon Nichara; Udomsubpayakul Umaporn; Choprapawon Chanpen (BMC, 2009)
Abstract Background Effects of television to language development in infants and toddlers, especially in the Asian children, are inconclusive. This study aimed to (a) study time spent on television in Thai infants and toddlers (age < 2 years), (b) investigate the association between time spent on television (as recommended by the American Academy of Paediatrics (AAP), < 2 hours per day) and language development in Thai 2-year-old children, and (c) explore parental perceptions on television toward their child's development. Methods Two hundred and sixty children and their parents were recruited into the study. Time spent on television and parental perceptions on television viewing toward their child's development were recorded during face-to-face and telephone interviews. Language development was assessed at the age of 2 years using the Clinical Linguistic Auditory Milestone Scale (CLAMS), and parents' report. Association between delayed language development and time spent on television viewing, as well as other various parameters such as gender, maternal education and family income, were analysed using a multivariate logistic regression model. Results Most Thai infants and toddlers watched television at the age of 6 months, 1 year and 2 years old (98.0, 95.3 and 96.7%, respectively). On average, 1-year-old children watched television 1.23 ± 1.42 hours per day. This increased to 1.69 ± 1.56 hours per day when they were 2 years old. However, watching television longer than 2 hours per day did not associate with delayed language development. On multivariate logistic regression analysis, gender (male) was the only significant factor associated with delayed language development (OR = 6.9, 95% CI = 1.5-31.3). Moreover, 75%, 71%, and 66% of Thai parents believed that television viewing yielded benefits to children's developments. Conclusion Thai children commenced watching television at an early age and the amount of television viewing time increased by age. Most parents had positive perceptions to television viewing. The study found no association between time spent on television viewing (≥ 2 hours per day) and delayed language development at the age of 2 years. Gender (male) was the only variable associated with delayed language development.